2011
DOI: 10.3109/10903127.2011.561411
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Serious Infection During Prehospital Emergency Care

Abstract: Including prehospital provider impression to objective physiologic factors identified three more patients with infection at the cost of overtriaging five. Future research should determine the effect of training or diagnostic aids for improving the sensitivity of prehospital identification of patients with serious infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Still, a brief patient history combined with a simple primary survey of clinical parameters should enable the EMS staff to recognize most of the critically ill patients with sepsis. 12 It is possible that EMS personnel and GPs did recognize sepsis but failed to document it, as we only assessed the data derived from electronic or paper records. Valuable information may have been given verbally to the ED staff without EMS personnel seeing the need for proper documentation.…”
Section: Discussionmentioning
confidence: 99%
“…Still, a brief patient history combined with a simple primary survey of clinical parameters should enable the EMS staff to recognize most of the critically ill patients with sepsis. 12 It is possible that EMS personnel and GPs did recognize sepsis but failed to document it, as we only assessed the data derived from electronic or paper records. Valuable information may have been given verbally to the ED staff without EMS personnel seeing the need for proper documentation.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that many EMS encounters hospitalized with severe sepsis were transported by basic life support providers, classified as "nonurgent," and did not receive pre-hospital intravenous access-even though the vast majority were diagnosed on hospital admission. This occurred on a backdrop of thousands of low-risk EMS encounters, among whom 40% were not transported to hospitals and 70% brought to hospitals were discharged from the emergency (12,19), highlights an urgent need for accurate recognition tools for severe sepsis. Although no "12-lead ECG" is available, biological platforms that include traditional biomarkers or molecular expression profiles may complement existing clinical tools to assist in sepsis case finding.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, no similar care coordination or pre-hospital management is widely adopted in severe sepsis. The uncertain burden of pre-hospital sepsis, difficulty in rapid diagnosis, and variable pre-hospital care and times are barriers to shifting the paradigm of sepsis care from the emergency department to the ambulance gurney (13,19).…”
mentioning
confidence: 99%
“…Despite spending almost 1 hour with the sickest patients, EMS personnel may be unaware they are transporting a patient with severe sepsis, a major barrier to testing patient or system interventions in pre-hospital sepsis (19). We observed that many EMS encounters hospitalized with severe sepsis were transported by basic life support providers, classified as "nonurgent," and did not receive pre-hospital intravenous access-even though the vast majority were diagnosed on hospital admission.…”
Section: Discussionmentioning
confidence: 91%
“…The changing burden, high case fatality rates, and frequent involvement of EMS in severe sepsis suggest it may deserve consideration along with acute cardiovascular disease and trauma in critical care system-level planning. For practicing EMS personnel, the ample pre-hospital care interval and large sepsis case volume highlight an understudied opportunity to optimize care (19). Few data or consensus exists to guide pre-hospital treatment or advanced notification of severe sepsis to hospitals (13,35,36), and the National EMS Research Agenda does not yet include topics related to infection or severe sepsis (37,38).…”
Section: Discussionmentioning
confidence: 99%